Incorporating Educational Means for Professional Ethics Into the Accounting Curriculum in Libya. - بالخير , د. إبراهيم أحمد; النعاس , أ. إبراهيم أحمد (Dirasat in Economics and Business, 2021)
The improvement of the acc-ounting education is a persistent effort to support and maintain the accounting profession. As part of this effort is to emphasise the ethics for the professional accountants to elevate the acco-unting profession up to the exp-ectations of the stakeholders.This paper is a contribution towards this improvement throu-gh incorporating ethical educati-on into accounting education curriculum. This issue of incorp-orating was raised by the Inter-national Federation of Accoun-tants to encourage its members to adopt the ethical education as a crucial component in the acco-unting education curriculum. This adoption could be by empl-oying the ethical education fra-mework that was issued by the International Accounting Educ-ation Standards Board (IAESB) (IFAC, 2006). This paper is an att-empt to propose the inclusion of the ethical education to the acco-unting education curriculum in Libyan accounting education. Data related to the courses requ-ired for accounting major in uni-versities and colleges were coll-ected. The analysis of the coll-ected data indicates that ethical education content is not offered by these universities and colleg-es in Libya. The paper recomm-ends the inclusion of ethical education into the Libyan acco-unting education, and open the issue for study and discussion in the accounting departments.